Handbook on cities and crime - Oberwittler, Dietrich; Wickes, Rebecca (Edward Elgar Publishing, 2025)
"With insightful contributions from eminent scholars in the field, this multidisciplinary Handbook provides an authoritative overview of scholarship on cities and crime. It discusses contemporary theoretical and methodological approaches to urban crime research, as well as its practical implications and psychological impacts. Synthesizing a wealth of international research, chapters cover aspects of urban crime ranging from immigration, disasters and gentrification, to more specific challenges such as adolescent delinquency, gangs and hate crime. Highlighting the diversity of crime in cities, the Handbook emphasises the need to broaden perspectives beyond those usually observed in the Global North. Expert authors evaluate future avenues for preventing and controlling crime in cities, including alternative approaches to policing, digital surveillance and smart cities. Incisive and forward-looking, the Handbook on Cities and Crime is a vital read for academics and students in criminology, sociology, human geography and urban studies. Scholars and practitioners in fields such as housing, policing and ethnography will also benefit greatly from its insights"-- Provided by publisher